2016
DOI: 10.5194/bg-2016-472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ocean Iron Fertilization Experiments: Past–Present–Future with Introduction to Korean Iron Fertilization Experiment in the Southern Ocean (KIFES) Project

Abstract: Abstract. Since the start of the industrial revolution, human activities have caused a rapid increase in atmospheric CO 2 concentrations, which have in turn been cited as the cause of a variety climate changes such as global warming and ocean acidification. Various approaches have been proposed to reduce atmospheric CO 2 concentrations. The 'Martin (or Iron) Hypothesis' suggests that ocean iron fertilization (OIF) should be an efficient method for stimulating the biological pump in iron-limited high nutrient-l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 85 publications
(205 reference statements)
0
3
0
Order By: Relevance
“…Technical feasibility is evaluated by considering current technological readiness (ranging from schemes at the concept stage to schemes already deployed) and for lead time until full potential effectiveness, i.e., the time needed to reach full implementation (ranging from days to decades; see section FIGURE 3 | Contemporary history of the global implementation of some ocean solutions. (A) Recent changes in the global cumulative offshore wind potential (European Wind Energy Association, 2011; Global Wind Energy Council, 2016), global cumulative surface of ocean iron fertilization experiment patches (Yoon et al, 2016), global area of avoided loss of mangroves (Valiela et al, 2001;Hamilton and Casey, 2016), rebuilding of fish stocks (Kleisner et al, 2013) (in % of total fish stocks), and global cumulative surface of MPAs (Boonzaier and Pauly, 2016) (in % of the global ocean surface). (B) Future progress needed to reach full implementation of targets for all measures above, i.e., 300 EJ year −1 for offshore wind, all ocean high nutrient and low chlorophyll areas for iron fertilization, 10 and 30% of the global ocean for MPAs (Convention for Biological Diversity, 2010; O'Leary et al, 2017), all overexploited and collapsed fish stocks in the process of rebuilding (in 2014, 46% of the total fish stock was overexploited or collapsed) (Cheung et al, 2017), and pre-disturbance extent of mangroves (Valiela et al, 2001).…”
Section: Technical Feasibility and Cost Effectivenessmentioning
confidence: 99%
“…Technical feasibility is evaluated by considering current technological readiness (ranging from schemes at the concept stage to schemes already deployed) and for lead time until full potential effectiveness, i.e., the time needed to reach full implementation (ranging from days to decades; see section FIGURE 3 | Contemporary history of the global implementation of some ocean solutions. (A) Recent changes in the global cumulative offshore wind potential (European Wind Energy Association, 2011; Global Wind Energy Council, 2016), global cumulative surface of ocean iron fertilization experiment patches (Yoon et al, 2016), global area of avoided loss of mangroves (Valiela et al, 2001;Hamilton and Casey, 2016), rebuilding of fish stocks (Kleisner et al, 2013) (in % of total fish stocks), and global cumulative surface of MPAs (Boonzaier and Pauly, 2016) (in % of the global ocean surface). (B) Future progress needed to reach full implementation of targets for all measures above, i.e., 300 EJ year −1 for offshore wind, all ocean high nutrient and low chlorophyll areas for iron fertilization, 10 and 30% of the global ocean for MPAs (Convention for Biological Diversity, 2010; O'Leary et al, 2017), all overexploited and collapsed fish stocks in the process of rebuilding (in 2014, 46% of the total fish stock was overexploited or collapsed) (Cheung et al, 2017), and pre-disturbance extent of mangroves (Valiela et al, 2001).…”
Section: Technical Feasibility and Cost Effectivenessmentioning
confidence: 99%
“…This approach has been investigated experimentally, by modelling and by observations of natural system behaviour (Keller et al 2014a;Bowie et al 2015;Tagliabue et al 2017). The 13 experimental studies to date (seven in the Southern Ocean, five in the Pacific, and one in the sub-tropical Atlantic) have shown that primary production can be, but is not always, enhanced by the addition of iron (Boyd et al 2007;Yoon et al 2016;GESAMP, 2019).…”
Section: Climate Mitigation In the Open Oceanmentioning
confidence: 99%
“…According to Wolff et al (2011), iron fertilization areas had higher levels of organic matter inputs to the ocean floor, including nutrients such as polyunsaturated fatty acids and carotenoids, and there were large deep-sea species found with greater densities and biomasses but less evenly distributed. However, iron fertilization poses several risks, in which the stored organic matter may degrade and produce harmful gases such as methane and nitrous oxide that affect the ecology of the ocean (Nogia et al, 2013;Yoon et al, 2016;Fuss et al, 2018). Besides, alterations in phytoplankton communities may affect nutrient cycling, light penetration, zooplankton grazing and organic matter accessibility to the coastal systems, which the consequences may spread to the downstream ecosystems (Scott-Buechler and Greene, 2019).…”
Section: Mitigation Of Global Warmingmentioning
confidence: 99%